Educational enrichment and ULD, strategies to attend diversity in presential return - Covarrubias Pizarro, Pedro; Garibay Moreno, Claudia Selene (IE Revista de Investigación Educativa de la REDIECH, 2021)
This paper offers an alternative for the educational attention that students will receive when they return to school in person, after the SARS-Cov-2 virus pandemic. Faced with an uncertain panorama about the conditions of return to the classroom and the diversity of the students, we reflect on the variables that will play a role in the achievement of learning. At first, the problems that have been experienced in the educational environment and the vulnerable situation of the students during confinement are described. Of this population, emphasis is placed on those who present a specific condition and make up the diversity in the classrooms. Subsequently, the normative documents issued by the Secretaría de Educación Pública in Mexico to regulate the return in person and the strategy of the state of Chihuahua are analyzed. The document sets out two alternatives to respond to diversity in the classroom, considering that the greatest challenge for teachers will be the organization and optimization of time and attention to diversity. These two strategies are educational enrichment and universal learning design as principles of diversified planning. Both proposals are congruent with the academic guidelines for the presential return.